The Effect of Financial Literacy on Financial Behavior and its Impact on Financial Decisions – The Case of Lebanese University Students - Nada, Jabbour Al Maalouf; Elia, Jean; Sawaya, Chadia (International Journal of Membrane Science and Technology, 2023)
Financial literacy is the comprehension of finance and attitudes toward financial opportunity and financial behavior. Financial acquaintance is crucial for making responsible financial decisions. In this challenging financial environment, we are living in, young people, particularly university students, must make challenging financial decisions that will impact their financial behavior. This study aims to examine the relationship between financial behavior and financial decision-making among Lebanese university students. The study is significant because it raises serious questions regarding the long-term effects of financial literacy on financial behavior and its impact on financial decision-making. The study adopted a quantitative methodology to accomplish its key goals. Students from various Lebanese universities were given a questionnaire. Using a convenience sampling method, a sample of five hundred ninety-eight participants was obtained. SPSS was used to analyze the data, namely Pearson correlation and regression analyses. The study's conclusions demonstrated the beneficial influence of financial literacy on financial behavior. Additionally, they demonstrated the beneficial effects of financial conduct on the financial judgments of university students in Lebanon. Thus, it is strongly advised that college students become financially literate so they may make wise financial decisions. Moreover, for Lebanon to be among the top countries with the highest financial literacy the Lebanese Ministry of Education and Higher Education should include within the curriculum of the intermediate and secondary classes some financial educational programs, workshops, and seminars. This will let students have exposure to basic financial knowledge and learn its significance and need in their financial decision-making.